Guest Perception of Service Quality Decline Due to Employee Multitasking in the Era of Digital Transformation in Star-Rated Hotels - Suyamto Suyamto; Dian Deliana; Erwin Purbosaputro; Sujatmiko Sujatmiko (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The development of digital technology in the hospitality sector has led to changes in employee work patterns, particularly related to multitasking practices in service activities. This condition must be able to influence the perception of service quality by guests, especially in face-to-face contact. Research Objective: This study aims to examine the effect of multitasking in service on the perception of service quality by guests in star-rated hotels. Research Design: A quantitative approach and exploratory survey design were used. Data were collected using an online questionnaire with a five-point Likert scale from 172 respondents obtained through purposive sampling. We focused on guests who stayed at star-rated hotels during the past year and had experience interacting directly with employees. Descriptive analysis and simple linear regression were used in examining the data. Based on the results, the employee multitasking variable was found to be at a high level and service quality was in the medium category. The Responsiveness and Empathy dimensions received the lowest scores compared to other dimensions. As we can see from the regression, employee multitasking negatively and significantly affected service quality (β = −0.487, P = 0.000). Thus, these results indicate that the more staff multitasked, the lower the service quality perceived by guests. These findings have implications for hotel management to balance employee workload so that service quality is not compromised.